2015
DOI: 10.1016/j.biortech.2015.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrochemically-assisted reductive dechlorination of 1,2-dichloroethane by a Dehalococcoides- enriched microbial culture

Abstract: g r a p h i c a l a b s t r a c t Keywords:Bioelectrochemical dechlorination 1,2-Dichloroethane Reductive dechlorination Microbial biocathode a b s t r a c tThe aim of this study was to verify the possibility to use a polarized graphite electrode as an electron donor for the reductive dechlorination of 1,2-dichloroethane, an ubiquitous groundwater contaminant. The rate of 1,2-DCA dechlorination almost linearly increased by decreasing the set cathode potential over a broad range of set cathode potentials (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The capability of the AQDS‐functionalized electrode to stimulate the reductive dechlorination of 1,2‐DCA by a mixed dechlorinating culture was assessed by means of batch experiments. The experiments were carried out in the 2‐chamber bioelectrochemical cell described previously . Initially, the working electrode's compartment of the bioelectrochemical cell was filled with 110 mL of anaerobic mineral medium and a 40 mL inoculum consisting of a 1,2‐DCA dechlorinating enrichment culture .…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…The capability of the AQDS‐functionalized electrode to stimulate the reductive dechlorination of 1,2‐DCA by a mixed dechlorinating culture was assessed by means of batch experiments. The experiments were carried out in the 2‐chamber bioelectrochemical cell described previously . Initially, the working electrode's compartment of the bioelectrochemical cell was filled with 110 mL of anaerobic mineral medium and a 40 mL inoculum consisting of a 1,2‐DCA dechlorinating enrichment culture .…”
Section: Methodssupporting
confidence: 86%
“…Recently, a new approach has been pursuit to tackle some of these disadvantages, which is based on the use of a potentiostatically controlled graphite electrode to selectively and efficiently deliver the needed electrons to the reductively dechlorinating microbial communities , . So far, the efficacy of this bioelectrochemical approach has been verified, at least at the laboratory scale, on several different chlorinated aliphatic hydrocarbons (CAHs), namely perchloroethene (PCE) , trichloroethene (TCE) , and even 1,2‐DCA , . In this respect, a previous study from our group has shown that 1,2‐DCA can be reductively dechlorinated to harmless ethene, via dihaloelimination, using a polarized graphite cathode (from –300 mV to –900 mV vs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundwater is often contaminated by a variety of organic and inorganic contaminants, for example, 1,4‐dioxane is often found co‐contaminated with chlorinated hydrocarbons (e.g., TCE and TCA; Stefan & Bolton, ; Zhang, Gedalanga, & Mahendra, ). Degradation of chlorinated hydrocarbons has been widely studied on cathodes of bioelectrochemical systems; however, the process generally needs supplying external voltage (Aulenta et al, ; Leitão et al, ; Pous, Balaguer, Colprim, & Puig, ). By generating electrical power during 1,4‐dioxane anodic degradation, power input for remediating 1,4‐dioxane and chlorinated hydrocarbon co‐contaminated groundwater would be reduced.…”
Section: Resultsmentioning
confidence: 99%
“…This system can be managed to achieve a complete mineralization of PCE in real groundwater in a continuous-flow mode, where highly-localized treatment zones are established (Aulenta et al, 2011;Lohner et al, 2011). A further improvement in energy efficiency can be achieved by establishing a direct delivery of electrons between the electrodes and degrading bacteria (Leitão et al, 2015) or channeled by other co-existed dechlorinating species (Patil et al, 2014).…”
Section: Organic Contaminant Degradationmentioning
confidence: 98%